Understanding GPS/GNSS : principles and applications - Kaplan, Elliott D.; Hegarty, C. (GNSS technology and applications series., 2017)
Providing a comprehensive treatment of the Global Navigation Satellite System (GNSS), this reference offers both a quick overview of GNSS essentials and an in-depth treatment of advanced topics exploring all the latest advances in technology, applications, and systems. --